Redesigning thiamin synthesis: Prospects and potential payoffs. (August 2018) - Hanson, Andrew D.; Amthor, Jeffrey S.; Sun, Jiayi; Niehaus, Thomas D.; Gregory, Jesse F.; Bruner, Steven D.; Ding, Yousong
Highlights: Thiamin is essential but unstable and so must be made continuously at high rates. Thiamin biosynthesis relies on suicide and near-suicide enzymes, THI4 and THIC. THI4 and THIC turnover impose high energy costs that cut biomass yield potential. Replacing THI4 and THIC with more efficient enzymes could therefore boost yield. There may be efficient natural and synthetic alternatives to THI4 and THIC. Abstract: Thiamin is essential for plant growth but is short-lived in vivo and energetically very costly to produce – a combination that makes thiamin biosynthesis a prime target for improvement by redesign. Thiamin consists of thiazole and pyrimidine moieties. Its high biosynthetic cost stems from use of the suicide enzyme THI4 to form the thiazole and the near-suicide enzyme THIC to form the pyrimidine. These energetic costs lower biomass yield potential and are likely compounded by environmental stresses that destroy thiamin and hence increase the rate at which it must be made. The energy costs could be slashed by refactoring the thiamin biosynthesis pathway to eliminate the suicidal THI4 and THIC reactions. To substantiate this design concept, we first document the energetic costs of the THI4 and THIC steps in the pathway and explain how cutting these costs could substantially increase crop biomass and grain yields. We then show that a refactored pathway must produce thiamin itself rather than a stripped-down analog because the thiamin molecule cannot be simplified without losing biological activity. Lastly, we consider possible energy-efficient alternatives to the inefficient natural THI4- and THIC-mediated steps.